O processo em meio reticular-eletrônico: o impacto da hipercomunicação na intimação dos advogados e no bloqueio judicial, resulta no aumento da eficiência endoprocessual? - Santos, Lisangela de Sousa (2024)
The concern with the democratization of popular procedural law through fundamental rights. With this in mind, the legislator, in the area of procedural law, increasingly sought to create mechanisms that can shorten the march of the judicial process. In our legal system, the New Code of Civil Procedure (CPC) by ordering the law that has the computerization of the judicial process comes with a democratic perspective of the civil process permeated with the presence of cyberculture. In this context of democratization of procedural law for fundamental rights, the discussion falls on the principle of procedural efficiency. Linked to this, the current news and a new perspective of discovery of the judicial process. Cyberculture enters the Law and establishes the presence of the Electronic Judiciary or new questions about how much faster the judicial process becomes when using this digital tool without allowing all the constitutional guarantees to be threatened. In view of the field presented here presented approaches, the proposed research, it will be possible to review the theory and its technology literature as areas of technology law; as well as empirical in order to verify the procedural efficiency in the face of the new context of cyberculture. Finally,understanding that an Electronic Judicial Process platform is a tool that aims to assist legal operators, thus, we aim at the conclusion of this work to find out, if in practice this is made more efficient the acts contained therein, so, Let's specifically study efficiency and for that we will verify the process and for that we will also verify the subpoena made, by the PJe system, we are more efficient in the efficiency of the lawyers, as we will verify if the interoperability of the PJe system is also increasing the efficiency of the online pen.